1986
DOI: 10.1128/jb.167.1.312-318.1986
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning, DNA sequencing, and enzymatic analyses of two Escherichia coli pyruvate oxidase mutants defective in activation by lipids

Abstract: Two Escherichia coli pyruvate oxidase (EC 1.2.2.2) mutant genes, poxB3 and poxB4, were cloned on plasmid pBR322. The poxB3 mutant oxidase which was described previously (Y. Y. Chang and J. E. Cronan, Jr., Proc. Natl. Acad. Sci. USA 81: [4348][4349][4350][4351][4352] 1984) was deficient in lipid activation but retained full catalytic activity.The poxB3 mutation was located in the C-terminal half of the gene, and the nucleotide alteration has been determined by DNA sequencing of this part of the gene and by com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

1987
1987
2013
2013

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…Furthermore, residue Gly35 in the Lactobacillus plantarum sequence, suggested to be a possible binding site for inorganic phosphate (47), is also unique to the lactobacterial pyruvate oxidases and is replaced by aspartate residues in the phosphate-independent pyruvate:quinone oxidoreductase enzymes. In contrast, a proline residue (Pro536) shown to be essential for lipid activation of the E. coli pyruvate oxidase (12) is conserved in all but the lactobacterial enzymes shown in Fig. 2.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, residue Gly35 in the Lactobacillus plantarum sequence, suggested to be a possible binding site for inorganic phosphate (47), is also unique to the lactobacterial pyruvate oxidases and is replaced by aspartate residues in the phosphate-independent pyruvate:quinone oxidoreductase enzymes. In contrast, a proline residue (Pro536) shown to be essential for lipid activation of the E. coli pyruvate oxidase (12) is conserved in all but the lactobacterial enzymes shown in Fig. 2.…”
Section: Discussionmentioning
confidence: 99%
“…The structure thus reveals that the C-terminal domain is held firmly in place by the half-barrel super secondary structure and a large number of hydrogen-bonding and electrostatic interactions evenly distributed over the whole sequence. Earlier mutagenesis data had already indicated that several residues of the C terminus (E 564 , R 572 ) and residues of the active center loop (A 467 ) interacting with the half-barrel motif play critical roles for membrane binding and activity (29,30). Most remarkably, many of the residues implicated in forming the proposed membrane-binding amphipathic helix (G 559 -D-E-V-I-E-L-A-K-T 568 ) are located in the sheet structure.…”
Section: Resultsmentioning
confidence: 99%
“…Like the E. coli enzyme, the C. glutamicum PQO is a homotetrameric flavoprotein containing TPP, and it is activated by Triton X-100, phosphatidylglycerol and dipalmitoyl-phosphatidylglycerol. In contrast, it does not reduce ferricyanide, which is routinely used for assaying the E. coli enzyme (1,9,75), and it probably uses a menaquinone instead of ubiquinone as the physiological electron acceptor (59). The C. glutamicum PQO activity was highest in cells grown on complex medium and about threefold lower when glucose was added to the complex medium or when the cells were grown on minimal medium containing different carbon sources, suggesting that the enzyme is regulated by the carbon source in the growth medium.…”
mentioning
confidence: 99%
“…This enzyme has been shown to be strongly activated by low concentrations of phospholipids and detergents (5,8,15,16,28), and the activation has been shown to be accompanied by conformational changes and alteration of various properties of the enzyme (11,12,74). Aside from extensive biochemical characterization of the E. coli PQO, the respective gene ( poxB) and its expression have been studied in detail (7,9,25). Expression of the poxB gene was dependent on sigma factor RpoS and thus induced in the stationary growth phase (7).…”
mentioning
confidence: 99%